Upaya Pencegahan Stunting Melalui Pemberian Makanan Tambahan Dengan Edukasi Tentang Stunting Pada Balita Di Desa Oben, Kecamatan Nekamese - Naingalis, Angela L.; Juwa, Maria M. Mue; Olla, Sinta Inriani; Nenogasu, Yeri Delsia; Pay, Frida S.; Zakiah, Ummu (Training & Research Institute - Jeramba Ilmu Sukses, 2024)
Stunting is a condition characterized by a child's lack of height compared to children his age. Put, stunting is a term for growth disorders in children. This community service aims to help mothers increase their knowledge and awareness about stunting. The method of service is carried out in the form of health education about stunting, PowerPoints, and LCDs, as well as the distribution of green Kajang and egg porridge at Oben Village. The targets of this service activity are mothers who have children under five. The number of mothers who participated in this service activity was 30. The result of this service is that the counseling material provided is good enough to increase the mother's knowledge and understanding, as evidenced by the increase in the average score after the post-test. The average pre-test score is 26.7, and the average post-test score is 83.3. It is necessary to provide similar counseling to mothers of toddlers.